Comparative Analysis of Rice Transformation Using Agrobacterium tumefaciens and Rhyzobium leguminosarum - Syamsidah Rahmawati; Osmat Azzam Jefferson; Didy Sopandie; S. Suharsono; Inez Hortense Slamet-Loedin (Indonesian Journal of Biotechnology, 2010)
This study was aimed to study the effectiveness of Rhizobium transformation system compared to the most widely used Agrobacterium mediated transformation system on three rice cultivars, Ciherang (Indica), Nipponbare (Japonica), and Rojolele (Javanica). Six day old calli induced from immature embryos were inoculated with Rhizobium leguminosarum bv trifolii ANU845 and Agrobacterium tumefaciens LBA288 that harbored with vector pCAMBIA 5106. This plasmid contained a minimum set of transfer machinery genes and had a gusplus and an hptII gene driven by 35S CaMV promoter in the T-DNA. The results showed that the transformation frequencies (number of PCR positive plants per number of calli inoculated) ranging from 0 to 12.05 % depend on the genotype and transfer agent used. The highest transformation frequency (12.05%) was obtained in Ciherang transformed with R. leguminosarum. Most of the transgenic rice obtainedby Rhizobium transformation were normal in morphology and fertile similar to those obtained by Agrobacterium transformation. Integration, expression and inheritance of transgenes were demonstrated by molecular and genetic analysis in T0 and T1 generations.Key words : Rhizobium leguminosarum, immature embryos, Agrobacterium tumefaciens